Clinical characteristics, treatment patterns, and outcomes in adult patients with germline BRCA1/2-mutated, HER2-negative advanced breast cancer: a retrospective medical record review in the United States - Obeid, Elias; Parikh, Rohan C.; Esterberg, Elizabeth; Arondekar, Bhakti; Hitchens, Abigail; Arruda, Lillian Shahied; Niyazov, Alexander; Whitaker, Kristen (Frontiers in Oncology, 2024)
Aim: To examine clinical characteristics, real-world treatment patterns, and health outcomes among patients with germline BRCA1/2 mutated human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer (ABC). Methods: A retrospective analysis was conducted using medical records from patients with HER2-negative ABC with BRCA1/2 mutation who received cytotoxic chemotherapy. Data were stratified into groups with triple-negative breast cancer (TNBC) or hormone receptor-positive (HR+)/ HER2-negative diagnoses. Time-to-event outcomes ([i.e., real-world progression-free survival [rwPFS] and overall survival [OS]) were calculated to summarize health outcomes. Results: When diagnosed with ABC, most patients were younger than 60 years (mean age = 57.3 years), were white (76.4%), and had a family history of BRCA-related cancer (71.5%). A total of 305 patient records were examined and 194 patients (63.6%) had advanced TNBC, and 111 patients (36.4%) had HR+/HER2-negative ABC. Chemotherapy was primarily used as first-line treatment for both subgroups, but the TNBC subgroup received poly (ADP-ribose) polymerase (PARP) inhibitors at triple the rate as a second-line treatment and double the rate as a third-line treatment compared with the HR+/HER2-negative subgroup. Two-year OS rates were similar between the TNBC (73.9%) and the HR+/HER2-negative subgroups (77.0%), and anemia, nausea, and neutropenia were the most commonly reported toxicities across all treatments. Conclusion: Clinicians should consider the use of targeted agents such as PARP inhibitors in earlier lines of therapy for ABC given the growing evidence that PARP inhibitors may improve PFS compared with chemotherapy while potentially offering a more manageable toxicity profile and improved quality of life.